The island cotton NBS‐LRR gene GbaNA1 confers resistance to the non‐race 1 Verticillium dahliae isolate Vd991. (9th February 2018) - Li, Nan‐Yang; ma, Xue‐Feng; Short, Dylan P. G.; Li, Ting‐Gang; Zhou, Lei; Gui, Yue‐Jing; Kong, Zhi‐Qiang; Zhang, Dan‐Dan; Zhang, Wen‐Qi; Li, Jun‐Jiao; Subbarao, Krishna V.; Chen, Jie‐Yin; et al.
Summary: Wilt caused by Verticillium dahliae significantly reduces cotton yields, as host resistance in commercially cultivated Gossypium species is lacking. Understanding the molecular basis of disease resistance in non‐commercial Gossypium species could galvanize the development of Verticillium wilt resistance in cultivated species. Nucleotide‐binding site leucine‐rich repeat (NBS‐LRR) proteins play a central role in plant defence against pathogens. In this study, we focused on the relationship between a locus enriched with eight NBS‐LRR genes and Verticillium wilt resistance in G. barbadense . Independent virus‐induced gene silencing of each of the eight NBS‐LRR genes in G. barbadense cultivar Hai 7124 revealed that silencing of GbaNA1 alone compromised the resistance of G. barbadense to V. dahliae isolate Vd991. In cultivar Hai 7124, GbaNA1 could be induced by V. dahliae isolate Vd991 and by ethylene, jasmonic acid and salicylic acid. Nuclear protein localization of GbaNA1 was demonstrated by transient expression. Sequencing of the GbaNA1 orthologue in nine G. hirsutum accessions revealed that all carried a non‐functional allele, caused by a premature peptide truncation. In addition, all 10 G. barbadense and nine G. hirsutum accessions tested carried a full‐length (∼1140 amino acids) homologue of the V. dahliae race 1 resistance gene Gbve1, although some sequence polymorphisms were observed . Verticillium dahliae Vd991 is a non‐race 1 isolate that lacks the Ave1 gene. Thus, the resistance imparted by GbaNA1 appears to be mediated by a mechanism distinct from recognition of the fungal effector Ave1.